BEYOND AUTOMATION: AI AS A STRATEGIC PARTNER IN TALENT DEVELOPMENT FOR KPO/BPO/ITES SECTOR - Mohasin, Khadija; Mane, Pravin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As artificial intelligence (AI) technologies mature, their role in talent development is undergoing a profound transformation—moving beyond operational automation toward strategic partnership in workforce growth. This study explores the evolving integration of AI-enabled solutions in KPO, BPO, and ITES sectors, with a particular emphasis on how organizations are leveraging these technologies to redefine human resource management (HRM) practices, widely regarded as a burgeoning outsourcing and technology hub, offers a fertile landscape for analyzing the complex dynamics between AI adoption, organizational preparedness, and stakeholder engagement. This research investigates the nuanced shift from AI as a task-oriented facilitator to AI as a co-creator of personalized learning and performance pathways. Through exploratory fieldwork comprising surveys, semi-structured interviews, and secondary data analysis, the study captures first-hand insights from HR managers, line managers, and operational staff across various outsourcing enterprises. Central to the analysis are three intersecting dimensions: (1) the perception of HR and line managers regarding AI’s strategic value in talent development; (2) organizational readiness for adopting AI-driven platforms in learning, performance management, and succession planning; and (3) ethical and psychological implications tied to AI-led interventions. These include concerns around algorithmic bias, transparency, employee trust, and emotional responses to automated evaluation mechanisms. The research foregrounds the perspectives of multi-HR managers and line managers to provide a balanced understanding of how human-AI collaboration is influencing the cultural, procedural, and strategic aspects of Talent development. Findings reveal a growing inclination among organizations to adopt hyper-personalized development frameworks, replacing traditional and one-size-fits-all training models. AI platforms are increasingly used to deliver real-time feedback, simulate contextual problem-solving scenarios, and provide just-in-time learning nudges aligned with evolving job roles. It proposes that strategic use of AI in talent development anchored in transparent governance and HR and Line Manager trust can help outsourcing firms in build resilient, future-ready workforces. The findings aim to inform not only policy-makers and organizational leaders but also researchers seeking to advance interdisciplinary frameworks for AI-Talent development integration.